Breaking employee's silence: A cross-level investigation of the role of socio-moral climate and negative affect at work - Silva, S.A.; Tavares, S. M.; Unterrainer,C.; Weber, W. (18th European Congress of Work and Organizational Psychology: “Enabling Change through Work and Organizational Psychology: Opportunities and Challenges for Research and Practice”., 2017)
Purpose This study examined the process underlying the relationship between socio-moral climate (SMC) and employees' silence behaviors. Using conservation of resources theory, we propose that negative affect at work mediates the effects of SMC on employees' quiescent and acquiescent silence. Design/Methodology We tested the model with a cross-level structural equation model based on a questionnaire data collected from 429 employees in 51 organizational contexts. Results The results revealed that SMC (at organizational level) is negatively related with both negative affect at work and employee's quiescent and acquiescent silence (both at individual level). Moreover, negative affect at work is positively associated with both employee's quiescent and acquiescent silence (at the within individual level). At the between (organization) level, negative affect was significantly related to acquiescence silence but not to quiescence silence. Therefore, our mediation hypotheses were only partially supported. Limitations The cross-sectional design and the correlational nature of the actual data prevent us from drawing causal and temporal inferences, making it difficult to rule out alternative explanations for the observed relationships. Research/Practical Implications Our results suggest that organizations may prevent employee silence by managing SMC in the workplace. Originality/Value This paper sheds some light on the affective processes that emerge from SMC and their role in explaining SMC’s potential impact on employee’s silence, thus expanding both the literature of SMC and silence.